First principles fluid modelling of magnetic island stabilization by electron cyclotron current drive (ECCD). (19th February 2016) - Février, O; Maget, P; Lütjens, H; Luciani, J F; Decker, J; Giruzzi, G; Reich, M; Beyer, P; Lazzaro, E; Nowak, S
Abstract: Tearing modes are MagnetoHydroDynamics (MHD) instabilities that reduce the performance of fusion devices. They can however be controlled and suppressed using electron cyclotron current drive (ECCD) as demonstrated in various tokamaks. In this work, simulations of island stabilization by ECCD-driven current have been carried out using the toroidal nonlinear 3D full MHD codextor-2f, in which a current source term modeling the ECCD has been implemented. The efficiency parameter, , has been computed and its variations with respect to source width and location were also computed. The influence of parameters such as current intensity, source width and position with respect to the island was evaluated and compared to the modified Rutherford equation. We retrieved a good agreement between the simulations and the analytical predictions concerning the variations of control efficiency with source width and position. We also show that the 3D nature of the current source term can lead to the onset of an island if the source term is precisely applied on a rational surface. We report the observation of a flip phenomenon in which the O- and X-points of the island rapidly switch their position in order for the island to take advantage of the current drive to grow.